2014
DOI: 10.3390/atmos5030635
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Mercury in Air and Precipitation across Canada: Patterns and Trends

Abstract: Atmospheric mercury (Hg) measurements from across Canada were compiled and analysed as part of a national Hg science assessment. Here we update long-term trends of Hg in air and precipitation, and present more extensive measurements on patterns and trends in speciated Hg species (gaseous elemental mercury-GEM, reactive gaseous mercury-RGM, and total particulate mercury on particles <2.5 μm-TPM 2.5 ) at several sites. A spatial analysis across Canada revealed higher air concentrations and wet OPEN ACCESSAtmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
68
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 79 publications
15
68
1
1
Order By: Relevance
“…S5a. Similarly, median concentrations of GOM and/or PBM measured at 10 sites in Canada during the years 2002-2011 were typically < 5 pg m −3 (Cole et al, 2014), corresponding with sample loadings of 3-9 pg. The corresponding median signal processing bias would be within −19 and −8 %, respectively, based on the fit in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…S5a. Similarly, median concentrations of GOM and/or PBM measured at 10 sites in Canada during the years 2002-2011 were typically < 5 pg m −3 (Cole et al, 2014), corresponding with sample loadings of 3-9 pg. The corresponding median signal processing bias would be within −19 and −8 %, respectively, based on the fit in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Within tropical regions, wet deposition has been shown to be a significant pathway for mercury from the atmosphere to both oceanic and terrestrial ecosystems, even in relatively low-mercury air and despite the low solubility of mercury in its elemental form (Fostier et al, 2000;Costa et al, 2012;Hansen and Gay, 2013;Soerensen et al, 2014;Shanley et al, 2015). Mercury "rainout" -or the tendency for mercury rainwater loading to decrease with increasing precipitation -has also been demonstrated in Mercury Deposition Network (MDN) data in North America (Glass and Sorensen, 1999;Prestbo and Gay, 2009) and positive correlations between GEM (TGM) and rainwater mercury have been reported in MDN data (GEM; Cole et al, 2014) and at Cape Point, South Africa (TGM; Brunke et al, 2016). Re-emission of any deposited mercury is likely to be inhibited throughout the wet season, as it has been shown that GEM emission from background mercury soils is suppressed when the soils are saturated (Briggs and Gustin, 2013).…”
Section: Overall Means and Seasonal Trendsmentioning
confidence: 99%
“…The atmospheric 90 lifetime of GOM due to reduction and deposition is on the order of days to weeks (Ariya et al, 2015;Horowitz et al, 2017;Shah et al, 2016). Although uncertainties remain, the shorter atmospheric lifetime and higher deposition fluxes of GOM translate to GEM making up the majority of TGM in most places (typically >95%) (Cole et al, 2014;Driscoll et al, 2013;Rutter et al, 2009;Slemr et al, 2015). As such any uncertainty related to the uptake of GOM by the PASs is 95 likely small.…”
Section: Passive Air Samplingmentioning
confidence: 99%